Hubungan Tingkat Kejadian Karies Gigi Dengan Status Gizi Anak Usia 6 -7 Tahun Di SD Inpres Kaniti Kecamatan Kupang Tengah Kabupaten Kupang - Ferdinan Fankari (JURNAL INFO KESEHATAN, 2018)
Dental caries is a dental and oral health problem for the majority of the Indonesian population. Dental caries affects most children. Caries that occur in children is often not treated or treated, resulting in a toothache. This condition can have an impact on the general health of the child where the frequency of eating will decrease, resulting in disruption of growth and development that will affect the nutritional status of the child. Nutritional problems are caused by many factors that are interrelated both directly and indirectly. Directly affected by infectious diseases and insufficient nutrition in quantity and quality, while indirectly influenced by the range and quality of health services, inadequate parenting, poor sanitation conditions and low food security at the household level. This study aims to determine the relationship between the incidence of dental caries in children with the nutritional status of children aged 6-7 years SDI Kaniti Kabupaten Kupang in 2016. Data collection was carried out by performing dental examinations and measuring height and weight. The incidence rate of dental caries aged 6-7 years old SDI Kaniti Kabupaten Kupang in 2016 was in the high category (30.76%) and very high (37.17%) with an average 3-6 cavities and nutritional status of children aged 6- 7 years SDN Kaniti Kabupaten Kupang in 2016 was categorized as obese (26.92%) and normal (67.94%), so there was no correlation between the incidence of dental caries on the nutritional status of 6-7-year-olds in Kaniti Regency Kupang in 2016 because children who had high and very high caries incidence has fat and normal nutritional status. It is recommended to conduct further research on the factors that influence the high incidence of dental caries in children aged 6-7 years at SDN Kaniti, Kupang Tengah District, Kupang Regency.